Molecular dynamics simulation of the material removal in the scratching of 4H-SiC and 6H-SiC substrates. (4th November 2020) - Tian, Zige; Chen, Xun; Xu, Xipeng
Abstract: Single crystal silicon carbide (SiC) is widely used for optoelectronics applications. Due to the anisotropic characteristics of single crystal materials, the C face and Si face of single crystal SiC have different physical properties, which may fit for particular application purposes. This paper presents an investigation of the material removal and associated subsurface defects in a set of scratching tests on the C face and Si face of 4H-SiC and 6H-SiC materials using molecular dynamics simulations. The investigation reveals that the sample material deformation consists of plastic, amorphous transformations and dislocation slips that may be prone to brittle split. The results showed that the material removal at the C face is more effective with less amorphous deformation than that at the Si face. Such a phenomenon in scratching relates to the dislocations on the basal plane (0001) of the SiC crystal. Subsurface defects were reduced by applying scratching cut depths equal to integer multiples of a half molecular lattice thickness, which formed a foundation for selecting machining control parameters for the best surface quality.